36.8k views
0 votes
Which expressions are equivalent to when x0? Check all that apply.

Which expressions are equivalent to when x0? Check all that apply.-example-1
User Gonki
by
5.5k points

2 Answers

4 votes

Answer:

The correct representation of the expression are:


  • (x+4)/(3)((x)/(6))

  • ((x)/(6))(x+4)/(3)

  • (x^2+4x)/(18)

Explanation:

We are given an algebraic expression as:


(x+4)/(3)รท
(6)/(x)

This expression could also be written as:


=((x+4)/(3))/((6)/(x))

We know that any expression of the form:


((a)/(b))/((c)/(d)) is given by:


((a)/(b))/((c)/(d))=(a* d)/(b* c)}

Hence, we get the given expression as:


=((x+4)/(3))/((6)/(x))=((x+4)* x)/(3* 6)\\\\=(x+4)/(3)* (x)/(6)

Also, on solving we get:


=((x+4)/(3))/((6)/(x))=(x^2+4x)/(18)

User Abuybuy
by
6.1k points
6 votes
we have that


((x+4))/(3) / (6)/(x) = (x*(x+4))/(3*6) \\ \\ = (( x^(2) +4x))/(18)

therefore

case a)

((x+4))/(3) * (x)/(6)
Is equivalent

case b)

(6)/(x) * ((x+4))/(3)
Is not equivalent

case c)

(x)/(6) * ((x+4))/(3)
Is equivalent

case d)

((2 x^(2) +4x))/(6)
Is not equivalent

case e)

((2 x^(2) +4x))/(18)
Is equivalent

Hence

the answer is


((x+4))/(3) * (x)/(6)



(x)/(6) * ((x+4))/(3)



((2 x^(2) +4x))/(18)

User Alfwatt
by
6.5k points